Juridical Study of Premarital on Joint Property which Made by Notary and Legal Consequences in The District of Kudus - Pulung Jati Kusuma; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Premarital agreements on joint property made before or during the marriage took place, the parties may determine the contents of the agreement, especially respect the innate property of each party in a premarital agreement. In Act No. 1 of 1974 About the Marriage of Article 29 paragraph (1) confirms that at the time or before the marriage took place two parties by mutual consent may submit a written agreement authorized by the employee registrar of marriage, after which it shall also apply to third parties lodged. Having made premarital agreement then the next must be registered in the district court clerk's office in legal marriages were held, the purpose of such registration in order to satisfy the principle of publicity. Background of the problem, authors conducted a study entitled